2003
DOI: 10.1042/bj20030763
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative screening of advanced glycation endproducts in cellular and extracellular proteins by tandem mass spectrometry

Abstract: Glycation of proteins forms fructosamines and advanced glycation endproducts. Glycation adducts may be risk markers and risk factors of disease development. We measured the concentrations of the early glycation adduct fructosyl-lysine and 12 advanced glycation endproducts by liquid chromatography with tandem mass spectrometric detection. Underivatized analytes were detected free in physiological fluids and in enzymic hydrolysates of cellular and extracellular proteins. Hydroimidazolones were the most important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
692
3
8

Year Published

2005
2005
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 586 publications
(738 citation statements)
references
References 38 publications
29
692
3
8
Order By: Relevance
“…Glycation, oxidation and nitration adduct residues of plasma protein and haemoglobin were measured in exhaustive enzymatic digests (50 μg protein equivalent) prepared as described previously (with control subjects for protease autolysis) [11]. Samples were assayed by liquid chromatography with triple quadrupole mass spectrometric detection (LC-MS/MS) with stable isotope-substituted internal standardisation as described previously [5]. Pentosidine, NFK and trp were measured by liquid chromatography with modified fluorimetric detection: the mobile phase was 0.1% trifluoroacetic acid with isocratic 10% acetonitrile from 0 to 20 min and a linear gradient of 10-50% acetonitrile from 20 to 50 min eluted through column 1 only at a flow rate of 0.4 ml/min.…”
Section: Measurement Of Protein Glycation Oxidation and Nitration Admentioning
confidence: 99%
See 4 more Smart Citations
“…Glycation, oxidation and nitration adduct residues of plasma protein and haemoglobin were measured in exhaustive enzymatic digests (50 μg protein equivalent) prepared as described previously (with control subjects for protease autolysis) [11]. Samples were assayed by liquid chromatography with triple quadrupole mass spectrometric detection (LC-MS/MS) with stable isotope-substituted internal standardisation as described previously [5]. Pentosidine, NFK and trp were measured by liquid chromatography with modified fluorimetric detection: the mobile phase was 0.1% trifluoroacetic acid with isocratic 10% acetonitrile from 0 to 20 min and a linear gradient of 10-50% acetonitrile from 20 to 50 min eluted through column 1 only at a flow rate of 0.4 ml/min.…”
Section: Measurement Of Protein Glycation Oxidation and Nitration Admentioning
confidence: 99%
“…Protein glycation, as well as protein oxidation and nitration, is thought to contribute to vascular cell dysfunction and the development of microvascular diabetic complications (retinopathy, nephropathy and neuropathy) [2][3][4]. Recent research has shown that protein glycation, oxidation and nitration are increased in cellular and ex-tracellular proteins in diabetes [5]. Cells maintain the quality and functional integrity of proteins by degradation and replacement of damaged proteins; oxidation and glycation are major types of physiological protein damage [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations